Modeling and experimental evaluation of a non-isothermal photocatalytic solar reactor: temperature effect on the reaction rate kinetics (2017)
(Eng) Mathematical modeling and experimental evaluation of temperature effects on photocatalytic degradation process and kinetic of a standard pollutants using solar radiation and suspended titanium dioxide were performed in a CPC reactor at pilot scale. The model of the system includes mass balance of the batch reactor with recycle, based on global isotropic parameters. The incident radiation was modeled using empirical models adjusted using experimental data from environmental reports and optimization algorithms in function of atmospheric variations. The effect of scattering-absorption of radiation inside the reactor was estimated by solving the radiative transfer equation. The effect of the temperature was modeled using a thermal balance coupled to heat transfer equations. The kinetic implemented model was a generalized model with a modification of the Arrhenius equation. It was found that the temperature affected the reaction rates by varying the oxygen concentration during the reaction. Process performance was improved under normal operating conditions without temperature control. The mathematical model and the established solution algorithm were highly predictive, generating correlation coefficients of 0.99 and errors below 2.5%.